Migration towards Europe and the “welfare magnet” : “Determinants of Turkish Migration to EU-15” - Jedličková, Kristýna; Klosová, Anna, 1942-; Villaverde Castro, José; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2015)
The purpose of this thesis is to analyse which factors drive migration from Turkey towards Europe and whether the welfare benefits play a major role in the decision making process. The analysis is based on a gravitation model of migration in log-log form. The FE and RE methods were employed as estimation techniques and the Hausman test enabled to distinguish them. The present problem of heteroscedasticity was solved by adjusting the model with robust standard errors. The most important determinants appear to be individual income which immigrants can earn in the states of the EU-15 and welfare benefits provided by the EU-15. The number of acquisition of citizenship, as a proxy for migration policy of countries the EU-15, plays also important role. The limitation of the model is that the rest of the variables are not statistically significant and therefore we do not consider them as important determinants.
Vedoucí práce: Anna Klosová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: economics of globalisation and european integration [obor dipl. práce]; diplomové práce; master's theses